Analysis of the Odor Purification Mechanism and Smoke Release of Warm-Mixed Rubber Asphalt - Tao Wang; Wenyu Bu; Zhiqiang Cheng; Rui Ma; Shengjia Xie; Zexiang Deng; Yuefeng Zhu; Yue Zhou (Applied Sciences, 2024)
This study focuses on the common key technologies of “environmentally friendly and resource-saving” asphalt pavement. Reactive asphalt deodorizers react with volatile chemicals with irritating odors in asphalt under high temperature conditions, converting them into stable and non-volatile macromolecules to remove odors and achieve a deodorizing effect. A goal is to develop clean asphalt pavement materials with the main characteristics of “low consumption, low emissions, low pollution, high efficiency”. In this experimental research, we used gas-emission detection devices and methods to detect and evaluate odor concentration, SO2, NO, volatile organic compounds, and other gases and volatile substances in the production and construction of clean asphalt and mixtures. By combining rheological experiments, mechanical experiments, and other means, this study investigates the effects of odor enhancers on the penetration, ductility, softening point, high-temperature rheological properties, construction, and workability of warm-mix asphalt and mixtures. Furthermore, infrared spectroscopy experiments are used to conduct in-depth research on the odor-enhancing mechanism of odor enhancers. The results indicate that the addition of odor enhancers has little effect on the penetration and softening point of asphalt and maintains the basic performance stability of asphalt. In terms of high-temperature rheological properties and construction workability, the addition of warm-mix agents has a significant impact on the high-temperature failure temperature and rotational viscosity of asphalt, while the influence of deodorizers is relatively small. At higher temperatures, the rotational viscosity increases with the increase in the amount of deodorant added. Functional group analysis shows that the newly added materials have little effect on the essential properties and chemical composition of asphalt. In addition, during the experimental process, it was found that the coupling effect and other chemical reactions between the deodorizing agent and the warm-mixing agent can effectively improve the degradation effect of harmful gases. After the coupling action of deodorant and the warm-mixing agent, the degradation rate of harmful gas can be increased by 5–20%, ensuring the stable performance of asphalt. The performance of powder deodorizing agent is better than that of liquid deodorizing agent, and an increase in the dosage of deodorizing agent will enhance the degradation effect. This study provides an important basis for a deeper understanding of the performance of warm-mix and odorless modified asphalt.